GENDER ROLES AND COOPERATIVE BEHAVIOUR - ALICE CALIN (Challenges of the Knowledge Society)
We live in a world where, without any doubt, the social, political, economical power are owned by men. Almost all the societies are more or less patriarchal and the gender roles are, generally speaking, well defined and assumed by the representatives of each gender. Also, we live in a world consisting of communities that could not exist in the absence of cooperation between individuals. However, we have to consider the fact that individuals are rational persons that choose to cooperate or not based on the gains brought by each of the possibilities. The purpose of this paper is to show that there is a correlation between the gender roles taught by each individual in childhood according to their sex and their cooperative behaviour. The hypothesis is that gender roles and cooperative behavior are interdependent and the way men and women cooperate is determined by the gender roles taught by each person since childhood according to the sex they were born. Perhaps we all heard that women are more gentle, more peaceful and more inclined to cooperation, all this being part of "their nature", while men are stronger, more practical, more rational and more likely to compete, also according to "their nature". In this paper I will assume that all these characteristics attributed to each gender are true, but I will question the nature’s responsibility in all these facts.